2021
DOI: 10.1155/2021/9216528
|View full text |Cite
|
Sign up to set email alerts
|

Extended Inflammation Parameters (EIP) as Markers of Immune System Cell Activation in Psoriasis

Abstract: Psoriasis is an inflammatory, autoimmune disease that affects approximately 2% of the population. The inflammation in psoriasis can be systemic, so despite a predominantly cutaneous manifestation, it also affects the internal organs. The diagnosis and monitoring of the disease are based on the clinical picture. To assess the disorders of other organs, additional tests need to be performed. Recently, the examination of blood morphology has been enriched with modern haematological parameters, i.e., Extended Infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our research, discussed in our previous article [ 12 ], clearly shows that an EIP-enriched CBC study in people with psoriasis can help improve the diagnostic interpretation of patient test results. It was decided to make similar observations for pemphigus.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Our research, discussed in our previous article [ 12 ], clearly shows that an EIP-enriched CBC study in people with psoriasis can help improve the diagnostic interpretation of patient test results. It was decided to make similar observations for pemphigus.…”
Section: Introductionmentioning
confidence: 82%
“…This study focuses on the evaluation of new hematological markers of inflammation-Extended Inflammation Parameters (EIP) in pemphigus. The evaluated parameters include NEUT-RI (Neutrophil Reactive Intensity, expressed in FI units, showing fluorescence intensity), NEUT-GI (Neutrophil Granularity Intensity, expressed in SI units, showing laser light scattering intensity), RE-LYMP (Reactive Lymphocytes, expressed as the number of cells per µL) and AS-LYMP (Antibody-Secreting Reactive Lymphocytes, expressed as the number of cells per µL) [ 12 ]. RE-LYMP parameter provides information on the amount of all reactive lymphocytes in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter strongly and positively correlated with the severity of the disease expressed in the PASI (r = 0.769, p = 0.045) and BSA (r = 0.703, p = 0.045) scales [ 8 ]. The above-mentioned results of the work, as well as our research described in this publication, show the huge diagnostic potential of EIP.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement takes into account the metabolic activity of neutrophils, the internal structure and the size of the cell [ 7 ]. It was revealed that these parameters can be used in diseases of various aetiology, such as psoriasis [ 8 ], pemphigus [ 9 ], type II diabetes, and gynaecological diseases (endometriosis, uterine fibroids) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes are the result of epidermal hyperplasia induced by T cells, capable of producing interleukins (IL)-17A, IL-22 and IFN-γ. The literature data show that the disease is caused by a wide variety of environmental, genetic, infectious, and even lifestyle factors [159][160][161]. Additionally, there is an evidence in the literature that HLA molecules are involved in the progression of psoriasis.…”
Section: The Role Of Hla-g In the Development Of Psoriasismentioning
confidence: 99%